2018
DOI: 10.3758/s13415-018-0567-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of implicit cognitive bias with cathodal tDCS to the left prefrontal cortex

Abstract: Implicit associations can interfere with cognitive operations and behavioral decisions without direct intention. Enhancement of neural activity with anodal transcranial direct current stimulation (tDCS) was proposed to reduce implicit associations by means of improved cognitive control. However, a targeted reduction of distractive implicit associations by inhibitory cathodal tDCS, recently shown in spatial-numerical associations, provides an interesting alternative approach to support goal-directed behavior wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…The results supported our hypothesis that automatic action tendency could be enhanced by excitatory DLPFC iTBS (upregulation of limbic system) and be abolished by inhibitory DLPFC cTBS (downregulation of limbic system). Our results were also consistent with previous transcranial direct current stimulation studies that anodal (excitatory) stimulation targeting the left DLPFC accelerates the reaction time in a congruent behavior (requiring the automatic action tendency; Gladwin et al, 2012), while cathodal DLPFC stimulation (inhibitory) reduced the difference in reaction time between the congruent and incongruent block and thus reduced the automatic action tendency (Schroeder et al, 2018). These studies and the present findings confirmed that the prefrontal network plays a major role in activating pre-existing programs associated with the automatic process (Schroeder et al, 2016;Ubaldi et al, 2015) and suggested that the cognitive bias with activation of impulsive system is enhanced by stimulating limbic system through left DLPFC excitatory iTBS.…”
Section: Effect Of Left Dlpfc Stimulationsupporting
confidence: 92%
See 1 more Smart Citation
“…The results supported our hypothesis that automatic action tendency could be enhanced by excitatory DLPFC iTBS (upregulation of limbic system) and be abolished by inhibitory DLPFC cTBS (downregulation of limbic system). Our results were also consistent with previous transcranial direct current stimulation studies that anodal (excitatory) stimulation targeting the left DLPFC accelerates the reaction time in a congruent behavior (requiring the automatic action tendency; Gladwin et al, 2012), while cathodal DLPFC stimulation (inhibitory) reduced the difference in reaction time between the congruent and incongruent block and thus reduced the automatic action tendency (Schroeder et al, 2018). These studies and the present findings confirmed that the prefrontal network plays a major role in activating pre-existing programs associated with the automatic process (Schroeder et al, 2016;Ubaldi et al, 2015) and suggested that the cognitive bias with activation of impulsive system is enhanced by stimulating limbic system through left DLPFC excitatory iTBS.…”
Section: Effect Of Left Dlpfc Stimulationsupporting
confidence: 92%
“…As mentioned above, our assumption is that it is possible to manipulate the excitability of limbic system bidirectionally (excitatory or inhibitory) by stimulating DLPFC using excitatory iTBS or inhibitory cTBS protocol. As a successful execution of the motivational behavior requires the automatic action tendency expressed in the limbic system with activation of the impulsive system (Ernst, Plichta, et al., 2013; Ernst & Fudge, 2009; Gladwin et al., 2012; Schroeder et al., 2018), we hypothesized that the upregulation of excitability in the limbic system with excitatory iTBS applied to the DLPFC will enhance the automatic action tendency. The downregulation of excitability of limbic system with inhibitory DLPFC cTBS will activate the reflective system and break the implicit association, therefore, will abolish the automatic action tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Originally termed the Spatial‐Numerical Associations of Response Codes (SNARC) effect, this behavioral signature is taken to reflect spontaneous encoding of biased task information in verbal working memory by most recent accounts (Abrahamse, van Dijck, & Fias, ; van Dijck & Fias, ; Schroeder, Dresler, et al, ; Schroeder, Nuerk, & Plewnia, ). According to this theoretical consideration, the activation of an implicit bias should draw on verbal working memory processes corroborated by the left prefrontal cortex (PFC), which was confirmed by the inhibitory cathodal tDCS to this region in four previous experiments (Schroeder et al, ; Schroeder et al, exp. 1 and 2; Schroeder, Nuerk, & Plewnia, ; Schroeder et al, ).…”
Section: Introductionmentioning
confidence: 78%
“…When using transcranial direct current stimulation (tDCS), a weak direct current is sent through the scalp which would slightly depolarize or hyperpolarize most resting membrane thresholds in a targeted region, mostly dependent on electrode position and current direction (Fertonani & Miniussi, ; Nitsche & Paulus, ; Priori, Berardelli, Rona, Accornero, & Manfredi, ). Accordingly, in neurocognitive investigations, hyperpolarizing cathodal tDCS to prefrontal regions can modulate certain cognitive processes, for example, to impair working memory processes (Wolkenstein, Zeiller, Kanske, & Plewnia, ; Zaehle, Sandmann, Thorne, Jäncke, & Herrmann, ) and reduce implicit associations (Schroeder, Nuerk, & Plewnia, ; Schroeder, Pfister, Kunde, Nuerk, & Plewnia, ) or response inhibition (Friehs & Frings, ; Hogeveen et al, ; Jacobson, Javitt, & Lavidor, ; Nieratschker, Kiefer, Giel, Krüger, & Plewnia, ). Thereby, this technology allows not only for a modulation of cognitive processing, but can also provide a critical test for a theory that predicts united or divided systems which should respond to regional brain stimulation in ensemble or produce dissociable modulations, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous study with healthy participants, 31 we anticipated an effect size (partial eta 2 ) of 0.25 for the 2 × 2 interaction between IAT block type and stimulation condition, reflecting the predicted reduction of the IAT score by cathodal tDCS. To obtain a power of 1 − β = 0.8 at α = 0.05, a minimum of 27 patients were required by the power analysis.…”
Section: Methodsmentioning
confidence: 99%